2019
DOI: 10.1126/science.aaw8562
|View full text |Cite
|
Sign up to set email alerts
|

Lack of therapeutic efficacy of an antibody to α 4 β 7 in SIVmac251-infected rhesus macaques

Abstract: Sustained virologic control of human immunodeficiency virus type 1 (HIV-1) infection after discontinuation of antiretroviral therapy (ART) is a major goal of the HIV-1 cure field. A recent study reported that administration of an antibody against α4β7 induced durable virologic control after ART discontinuation in 100% of rhesus macaques infected with an attenuated strain of simian immunodeficiency virus (SIV) containing a stop codon in nef. We performed similar studies in 50 rhesus macaques infected with wild-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 18 publications
6
34
2
Order By: Relevance
“…The effect of anti-α4β7 mAb administered in SIVinfected RMs during ART continues to be a highly debatable issue. While an earlier study showed that this treatment can limit viral rebound after ART interruption (21), more recent pre-clinical (23)(24)(25) and clinical (41) studies did not show any significant benefit from anti-α4β7 mAb treatment in ARTsuppressed, HIV-infected individuals or SIV-infected RMs in inducing viral remission in the absence of ART (42). Recently, using samples obtained from various gastrointestinal sites from IBD/CD patients, it was found that anti-α4β7 therapy led to a significant reduction of lymphoid aggregates, mostly in the terminal ileum (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of anti-α4β7 mAb administered in SIVinfected RMs during ART continues to be a highly debatable issue. While an earlier study showed that this treatment can limit viral rebound after ART interruption (21), more recent pre-clinical (23)(24)(25) and clinical (41) studies did not show any significant benefit from anti-α4β7 mAb treatment in ARTsuppressed, HIV-infected individuals or SIV-infected RMs in inducing viral remission in the absence of ART (42). Recently, using samples obtained from various gastrointestinal sites from IBD/CD patients, it was found that anti-α4β7 therapy led to a significant reduction of lymphoid aggregates, mostly in the terminal ileum (43).…”
Section: Discussionmentioning
confidence: 99%
“…IL-21 and anti-α4β7 mAbs have been previously administered as single interventions in naive or SIV-infected RMs with an acceptable safety profile (10,18,(21)(22)(23)(24)(25). However, combined administration of the two reagents has not yet been tested.…”
Section: The Combined Administration Of Il-21 and Anti-α4β7 Mab Is Samentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking of α4β7 in monkey models showed promise for prevention of SIV infection and for viral control in SIV-infected monkeys [39,40]. However, the latter results were not substantiated in recent studies of nonhuman primates [41][42][43] or HIV-infected patients [44].…”
Section: Expression Of Lfa-1 Integrin On Cd4+ T Cells Promotes Hiv Enmentioning
confidence: 97%
“…(3) have received ART for between 2 and 10 years; (4) have no other significant comorbidity; (5) are receiving no other immune-modulating treatments; (6) have wellcontrolled HIV infection as defined by stable pVL of <50 copies/mL and CD4 counts >500 cells/µL with nadir CD4 counts >200 cells/µL. Adults may be male, female or transgender.…”
Section: Inclusion Criteriamentioning
confidence: 99%